# Calc, Implicit Differentiation

posted by .

Regard y as independent variable and x as dependant variable and find the slope of the tangent line to the curve (4x^2 + 2y2)^2 - x^2y = 4588 at point (3,4).

Here's what I did:

2(8x(dy/dx) + 4y) -2x(dx/dy)y + x^2 = 0
16x(dx/dy) + 8y - 2x(dx/dy)y = -x^2
16x(dx/dy) - 2x(dx/dy)y = -x^2 - 8y
(dx/dy)(16x -2xy) = -x^2 - 8y
(dx/dy) = (-x^2 - 8y)/(16x -2xy)

But this doesnt work.

You have
(4x2 + 2y2)2 - x2y = 4588
It appears you started correctly and you know what you want, dy/dx, but I don't think you did the correct calculations.
It might help to think of this as
(f(x) + g(y))2 - h(x)*y = C
where f(x) = 4x2, g(y)=2y2 and h(x)=x2.
Then the differentiation should go
2(f(x) + g(y))*d/dx(f(x) + g(y)) - h(x)*dy/dx -h'(x)y = 0
Then f'(x)=8x, d/dx g(y)=g'(y)*dy/dx and h'(x)=2x
What I suggest, and this what I've done for real long expressions, is to write the symbols out, do the differentiation on the symbols, then substitute them into your equation.
Does this help?

## Similar Questions

1. ### calculus; implicit differentiation

Use implicit differentiation to find the slope of the tangent line to the curve at the point (4,1) -1x^2 - 4xy + 3y^3 = -29 I differentiated both sides and solved for dy/dx and got 2x-4y/9y^2-4x. Then I plugged in X and Y and got -4/7 …
2. ### calculus

Regard y as the independent variable and x as the dependent variable and use implicit differentiation to find dx/dy. y sec(x) = 9x tan(y)
3. ### math

use implicit differentiation to find the slope of the tangent line to the curve (y)/(x-7y)=x^6+5 at the point (1,6/43)
4. ### Calculus

(y/(x+9y))= (x^2)-7 at the point (1, -6/55) Use implicit differentiation to find the slope of the tangent line to the curve
5. ### Calculus

Regard as the independent variable and as the dependent variable and find the slope of the tangent line to the curve (x^2 + y^2)^2 - 4x^2 y = 225 at the point (x,y) = (4,1) Thank you very much for helping me.
6. ### Implicit Differentiation

Use implicit differentiation to find the slope of the tangent line to the curve y/x+6y=x^2–6 at the point (1,–5/31) . Again i think i'm messing up with the algebra here. I used quotient rule to get [(x+6y)(y')-(y)(1+6y')]/(x+6y)^2=2x …
7. ### Calculus ap

Use implicit differentiation to find the slope of the tangent line to the curve XY^3 + XY = 5 at the point (3,2) .
8. ### Math

Use implicit differentiation to find the slope of the tangent line to the curve y/( x + 4 y) = x^4 – 4 at the point (1,-3/13)
9. ### Math

Use implicit differentiation to find the slope of the tangent line to the curve y/( x + 4 y) = x^4 – 4 at the point (1,-3/13)
10. ### Math (Implicit Differention)

use implicit differentiation to find the slope of the tangent line to the curve of x^2/3+y^2/3=4 at the point (-1,3sqrt3)

More Similar Questions